(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The research on the hydro-geomorphology, sediment transport and human impact of large rivers has recently increased in South America. The GLOCOPH (Global Commission on Continental Paleohydrology) Working Group on Large Rivers chaired by us, organized Symposiums and Field Conferences on key large fluvial systems since 1997 such as the Paraná (1997 and 2006), the Araguaia (1999) and the Amazon (2003). Presently, the activities of GLOCOPH are also linked to TERPO (Terrestrial Processes, Deposits and History) Program supported by the Commission of INQUA- Focus area group Hydrological change and climate. Additionally, joint efforts were made with the IGCP Project 518 Fluvial sequences as evidence for landscape and climatic evolution in the Late Cenozoic and two important meetings were organized in China and Brazil during 2006 when the Paraná River Field Conference, an activity related to the GLOCOPH International Symposium, was held at Guarulhos.